2000
DOI: 10.1042/cs0990019
|View full text |Cite
|
Sign up to set email alerts
|

The angiotensinogen gene 235T variant is associated with an increased risk of restenosis after percutaneous transluminal coronary angioplasty

Abstract: The therapeutic benefit of percutaneous transluminal coronary angioplasty (PTCA) is limited by restenosis in 30-40% of patients. The underlying mechanisms are currently not well understood. Besides clinical and angiographic variables, genetic factors may be involved. In the present study, we investigated the associations between the angiotensinogen T174M and M235T, the angiotensin I-converting enzyme (ACE) I/D and the angiotensin II type 1 receptor A1166C gene polymorphisms and restenosis in 511 patients who h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Patients who bear the DD genotype of the ACE gene and who are thus genetically prone to increased ACE activity [14] were initially suggested to have a greater risk of restenosis after percutaneous coronary angioplasty compared to patients with the ID or II genotype [21]. However, larger and more rigorous studies [22][23][24] found weaker associations between the ACE DD genotype and restenosis after percutaneous coronary angioplasty, with or without additional stenting. In accordance, a meta-analysis reported an inverse correlation between study population size and magnitude of relative risk associated with I/D polymorphism [25].…”
Section: Discussionmentioning
confidence: 99%
“…Patients who bear the DD genotype of the ACE gene and who are thus genetically prone to increased ACE activity [14] were initially suggested to have a greater risk of restenosis after percutaneous coronary angioplasty compared to patients with the ID or II genotype [21]. However, larger and more rigorous studies [22][23][24] found weaker associations between the ACE DD genotype and restenosis after percutaneous coronary angioplasty, with or without additional stenting. In accordance, a meta-analysis reported an inverse correlation between study population size and magnitude of relative risk associated with I/D polymorphism [25].…”
Section: Discussionmentioning
confidence: 99%
“…In the initial study [Völzke et al, 2000], carriers of the c.803C variant had an odds ratio for developing restenosis after PTCA of 1.43 (95% confidence interval 1.06-1.93) when compared to c.803TT homozygotes. The association of the c.803C variant with an increased risk of restenosis was corroborated in a follow-up study [Hertwig et al, 2002] involving all those patients from the previous study [Völzke et al, 2000] who had suffered from restenosis and were consecutively subjected to a second PTCA procedure. In the follow-up study [Hertwig et al, 2002] carriers of the c.803C variant had an odds ratio for developing recurrent restenosis after repeated PTCA of 2.56 (95% confidence interval 1.11-5.89) when compared to TT homozygotes.…”
Section: Gross Et Al [2004]mentioning
confidence: 98%
“…However, most of the studies were relatively small and had a limited statistical power to detect a true relation. More recently, a study [Völzke et al, 2000] comprising 511 patients found restenosis in 23% of patients with the ACE Ã I/I genotype, 32% of patients with the ACE Ã I/D genotype and 38% of patients with the ACE Ã D/D genotype. While these data are reminiscent of a gene-dose effect for the D allele, the relation between the I/D sequence variation in the ACE gene and the risk of restenosis did not attain statistical significance after adjustments for confounders had been performed.…”
Section: Gross Et Al [2004]mentioning
confidence: 99%
See 2 more Smart Citations